Study of Tenderization Method of Old Goat Meat - Setyawardani, T; Haryoko, I (ANIMAL PRODUCTION, 2005)
The objective of the study was to investigate the effectiveness of tenderization methods on several characteristics of goat meat.  A total of 6 goats (approximately 3 years of age) were used in the study.  The meat was obtained from the hind leg (m. biceps femoris).  Treatments were arranged in a Completely Randomized Design (CRD) with 6 replicates in each treatment.  The treatments were P0: control, P1: the meat was submerged in pineapple juice extract, P2: the meat was electrically stimulated, and P3: the meat was injected with CaCl2 solution.  The variables measured were tenderness (mm/g/s), pH, water holding capacity (%), cooking losses (%), moisture content (%) and dissolved protein content (μg/ml).  Data obtained were analyzed using Analysis of Variance and Least Significant Difference compare the differences between means.  The result showed that treatments significantly (P<0.01) affected the meat tenderness, pH and water holding capacity but not significantly (P>0.05) affected meat cooking losses, moisture content and dissolved protein.  It can be concluded that injection CaCl2 was more effective in improving the tenderness of old goat meat. . (Animal Production 7(2): 106-110 (2005) Key Words : Tenderization Method, Pineapple Juice Extract, Goat meat, CaCl2, Electrical Stimulation